A rationale for the treatment of short stature in children with the combination of recombinant human growth hormone (rhGH) and recombinant human insulin-like growth factor-I (rhIGF-I) - Bright, George M.; Fierro-Renoy, Juan Francisco (Growth hormone & IGF research, 2020)
Both rhGH and rhIGF-I are signaling molecules with the capacity to restore the rate of growth in certain subsets of slowly growing children. In some instances, heights attained at or near the time of cessation of linear growth are indistinguishable from the height distribution of the community as a whole or from the height distribution expected based on the heights of biological parents. The GH: IGF-I signaling system is sequential, forming a continuous loop wherein GH will stimulate production of IGF-I and IGF-I will inhibit production of GH. This feature suggests that a deficiency of GH will be accompanied by a deficiency of IGF-I and that treatment of GH deficiency with rhGH will restore IGF-I and the subnormal growth of combined GH: IGF-I deficiency. Although logical, this proposition is not always true. rhGH and rhIGF-I are distinct polypeptides, with distinct cell surface receptors and distinct intracellular signaling pathways both capable of amplifying distinct, yet overlapping, patterns of gene replication, protein synthesis and metabolic activities. These features suggest that neither treatment with rhGH nor rhIGF-I alone will invariably recapitulate the combined activities of the GH: IGF-I system, At the present time, this proposition appears both logical and true. The possibility that combined rhGH and rhIGF-I treatment can accomplish that which neither monotherapy can has been examined in gene knock-out experiments in animals and direct comparisons of GH, IGF-I and combined GH: IGF- treatments in animals and in children with short stature, normal GH and low IGF-I (primary IGF-I deficiency). In these experimental models, the growth rates with combined rhGH and rhIGF-I treatment exceed those of either monotherapy. The extent to which this proposition can be generalized to various short stature populations remains to be determined.